Knowledge and Implications of Cemetery Policies among Workers of Baguio City Public Cemetery, Philippines - Dizon, Kurt Zeus L. (Public Governance, Administration and Finances Law Review, 2023)
Cemeteries in the Philippines are usually under the jurisdiction of local government units (LGUs). Among their jurisdiction is managing cemetery workers. The cemetery workers being part of the informal sector are a concern for LGUs since activities within the sector are unknowledgeable to government policies and prone of noncompliance to it. Thus, the study is anchored on determining if cemetery workers of Baguio know the policies governing cemeteries. The study employed both a quantitative and qualitative design, particularly through surveyquestionnaires and interviews. The data shows that the respondents are moderately knowledgeable on the identified cemetery policies. This is because attached offices of Baguio LGU have a constant practice of communicating and orienting the workers on the cemetery policies. Although workers are moderately knowledgeable and the LGU exerts effort and initiatives in communicating with the cemetery workers, some problems still persist due to misinterpretation and stubbornness among the workers.